Laboratory animal facility management - KOSTOMITSOPOULOS (Ν.Γ. ΚΩΣΤΟΜΗΤΣΟΠΟΥΛΟΣ), N. G. (Journal of the Hellenic Veterinary Medical Society, 2017)
The successful management of a laboratory animal facility is based on the design and implementation of a management program, which in most cases covers the minimum legislative requirements and goes further, in order to achieve more in the field of animal welfare. A complete management program should consist of the following main points: a) Monitoring of animal housing, the macro- and microenvironment of the animals, b) veterinary medical care, c) monitoring of electromechanical equipment and the overall construction of the animal facility, and designing of emergency and disaster plans, d) monitoring of the overall program by the Institutional Animal Care and Use Committee responsible to oversee and evaluate the management program of the facility, e) education and training of personnel and f) the implementation of an occupational health and safety program.